A wearable functional electrical stimulation device with a movable electrode for motor point tracking - Liu, Yue; Ebihara, Shin; Sugi, Masao; Yokoi, Hiroshi; Jiang, Yinlai (Frontiers in Bioengineering and Biotechnology, 2026)
Functional electrical stimulation is widely applied in the rehabilitation of individuals with cerebrovascular disease or spinal cord injury but is limited by rapid muscle fatigue. We present a novel stimulation strategy based on real-time motor point tracking using a wearable functional electrical stimulation device with a movable electrode. A crank–slider mechanism drives the electrode to follow the biceps brachii motor point trajectory according to elbow joint angle, aiming to optimize stimulation site and reduce fatigue. Seven healthy male participants compared this approach with time-shifted and joint angle–shifted stimulation. Muscle performance was evaluated by maximum voluntary contraction, change in elbow joint angle, and subjective comfort assessed on a visual analogue scale. Results showed that motor point tracking significantly reduced fatigue and improved comfort compared with conventional methods, supporting its potential to enhance functional electrical stimulation–based upper limb rehabilitation.